Advances in industrial & labor relations - Gollan, Paul J.; Kaufman, Bruce E.; Lewin, David 1943- (Emerald, 2010)
Continuing the tradition of Advances in Industrial and Labor Relations (AILR) this volume presents a rich mix of different approaches in industrial relations scholarship covering labor history, theory, quantitative and qualitative analysis. The range of papers in this volume potentially has significant implications for labour research and policy. The themes in this volume cover important social, economic and business perspectives raising critical issues from historical to contemporary debates covering issues such as union recognition and investor reaction, human resource management and organisational performance in the healthcare industry, employer associations, labor-related human rights and standards compliance in developing countries, work identity and sexual diversity, paradigm shifts in industrial relations and contract arbitration in Canada. This diverse range of themes provides not only an informative and useful contribution to our existing knowledge but raises important issues for contemporary debates in political and economic forums.